Poor sleep is associated with exaggerated cortisol response to the combined dexamethasone/CRH test in a non-clinical population - Hori, Hiroaki; Teraishi, Toshiya; Sasayama, Daimei; Ozeki, Yuji; Matsuo, Junko; Kawamoto, Yumiko; Kinoshita, Yukiko; Hattori, Kotaro; Higuchi, Teruhiko; Kunugi, Hiroshi (Journal of psychiatric research, 2011)
Although sleep disturbance has been shown to be associated with psychological distress and the hypothalamic-pituitary-adrenal (HPA) axis function, the simultaneous relationship between sleep, distress and HPA axis function is less clear. Here we examined the relationship between sleep quality as assessed with the Pittsburgh Sleep Quality Index, psychological distress as assessed with the Hopkins Symptom Checklist, and cortisol responses to the dexamethasone (DEX)/corticotropin-releasing hormone (CRH) test in 139 non-clinical volunteers. Poor sleep was significantly correlated with greater cortisol response to the combined DEX/CRH challenge, but not with the cortisol level just before CRH challenge. When subjects were divided into three groups based on the suppression pattern of cortisol (i.e., incomplete-, moderate-, and enhanced-suppressors), poor sleep was significantly associated with the incomplete suppression in women while no significant association was found between sleep and the enhanced suppression. The association between poor sleep and exaggerated cortisol response to the CRH challenge became more clear in the regression analysis where the confounding effect of psychological distress was taken into consideration. These results indicate that poor sleep would be associated with exaggerated cortisol reactivity. The observed association of poor sleep with reactive cortisol indices to the CRH challenge, but not with the cortisol level after DEX administration alone, might add to the well-established evidence demonstrating the role of CRH in the regulation of sleep. Our findings further suggest that the mediation model would work better than the bivariate approach in investigating the relationship between sleep, distress and HPA axis reactivity.